REPRODUCTIVE BIOLOGY OF THE YELLOW RASBORA (Rasbora lateristriata) INHABITAT OF THE NGRANCAH RIVER, KULON PROGO REGENCY - Djumanto Djumanto; Eko Setyobudi; A. A. Sentosa; N. Nirwati (Jurnal Perikanan Universitas Gadjah Mada, 2008)
The purpose of this research was to identify the reproductive biology in the yellow rasbora (Rasbora lateristriata) in habitat of the Ngrancah River. To identify spawning events and embryo development, direct observation was employed during the spawning season in their natural environment, and then fertilized egg was incubated insitu. Spawning seasons underwent correspond to the end of rainy season and early dry season which characterized by clean freshly water and low temperature. The result showed that during spawning season, the broodfish migrated from Sermo Reservoir upward to the main river to find out the spawning site. In the early morning between 03.00 and 05.00 AM, the broodstock moved to the spawning site, then making aggregation and both female and male released their gametes in the shallower place. The aggregations were consisting around of 1 female and 3 males. The fertilized eggs would cleavage, and then embryo developed and yolk sac larval hatched within 23 hours at 27oC. The knowledge about spawning events of yellow rasbora may be used for improved management tools in the future.